2021
DOI: 10.3892/ol.2021.12734
|View full text |Cite
|
Sign up to set email alerts
|

Novel brd4 inhibitors with a unique scaffold exhibit antitumor effects

Abstract: Since bromodomain containing 4 (brd4) has been considered as a prominent cancer target, numerous attempts have been made to develop potent brd4 bromodomain inhibitors. The present study provided a novel chemical scaffold which inhibited brd4 activity. Mid-throughput screening against brd4 bromodomain was performed using alpha-screen and homogeneous time-resolved fluorescence assays. Furthermore, cell cytotoxicity and xenograft assays were performed to examine if the compound was effective both in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…Recently, Zhou et al [ 75 ] noted that JQ-1 suppressed proliferation, migration and invasion of GC cells via targeting RUNX2/NID1 axis, while BET inhibitor AZD5153 inhibited GC metastasis by regulating Mus81 at both RNA and protein levels[ 76 ]. Kim et al [ 77 ] revealed new BRD4 inhibitor that showed efficiency in I-BET762 resistant GC cell lines[ 77 ]. Additionally, through blocking the expression of c-MYC and YAP1, JQ-1 reduced gastric adenocarcinoma cell growth induced by Gal-3, and the anti-cancer activity could be improved in combination with YAP inhibitors[ 78 ].…”
Section: Bet Inhibitors In Gi Cancersmentioning
confidence: 99%
“…Recently, Zhou et al [ 75 ] noted that JQ-1 suppressed proliferation, migration and invasion of GC cells via targeting RUNX2/NID1 axis, while BET inhibitor AZD5153 inhibited GC metastasis by regulating Mus81 at both RNA and protein levels[ 76 ]. Kim et al [ 77 ] revealed new BRD4 inhibitor that showed efficiency in I-BET762 resistant GC cell lines[ 77 ]. Additionally, through blocking the expression of c-MYC and YAP1, JQ-1 reduced gastric adenocarcinoma cell growth induced by Gal-3, and the anti-cancer activity could be improved in combination with YAP inhibitors[ 78 ].…”
Section: Bet Inhibitors In Gi Cancersmentioning
confidence: 99%